Давидові псалми в інтерпретації Ліни Костенко - Дюжева, К. (Літературознавчі обрії. Праці молодих учених, 2010)
The article studies king David’s psalms’ transformation in the light of the author’s personality. There is a study of national, politic context and Christian myths, poetic interpretation in the work. The concept of parallel comparison for the Psalter’s text and the poetry of Lina Kostenko is used. We can trace poet’s credo and her self-analyzing in a little investigated triptych of poetry «Psalms of David».